Determination of soil water hydraulic parameters from infiltration data. Issue 2 (8th June 2021) - Gao, Yan; Chang, Kai; Xing, Xuguang; Liang, Jiaping; He, Nian; Ma, Xiaoyi
Abstract : Purpose: Traditional laboratory measurements of soil water diffusivity ( D ) and soil water retention curve (SWRC) are always time-consuming and labor-intensive. Therefore, this paper aims to present a simple and robust test method for determining D and SWRC without reducing accuracy. Design/methodology/approach: In this study, a D model of unsaturated soil was established based on Gardner–Russo model and then a combination of Gardner–Russo model with one-dimensional horizontal absorption method to obtain n and a parameters of Gardner–Russo model. One-dimensional horizontal absorption experiments on loam, silt loam and sandy clay loam were conducted to obtain the relationships between measured infiltration rate and cumulative infiltration with wetting front distance. Based on the obtained relationships, the measured infiltration data from the one-dimensional horizontal absorption tests were used to calculate n and a parameters and further constructing D and SWRC. Findings: Both the calculated D and SWRC inversed from the infiltration data were in good agreement with the measured ones that obtained from the traditional horizontal absorption method and the centrifuge method, respectively. Error analysis indicated that only the infiltration data are enough to reliably synchronously determine D and SWRC. Originality/value: A simple and robust method is proposed for synchronous determination of soil water diffusivity and water retention curve.